Keputusan Majelis Pengawas Notaris Sebagai Bentuk Keputusan Tata Usaha Negara - Fahrul Fahrul (Magister Kenotariatan, Universitas Jambi, 2019)
Official Notary Public is authorized to make an authentic certificate and other authority as defined in the Act that the notary appointed by the government to serve the public interest and for the manufacture of authentic Akata. Notary Supervisory Council is an arm of the Ministry of Law and Human Rights, in this case the Supervisory Council received delegation by the Minister of Justice and Human Rights to conduct supervision and inspection of the Notary. In performing its duties, Council of Trustees has the authority to conduct surveillance, inspection and sanction against Notaries in running his alleged violation of the provisions of Law Notary. Authority in phases, namely: MPD, MPW, MPP. Supervisory authority Regional Assembly (MPD) under Article 69,70,71Undang Notary Act and the Regulation of the Minister of Justice and Human Rights of the Republic of Indonesia Number M.02.PR.08.10 2004 under Article 14,15,16,17. Regional Supervisor Assembly (MPW) provided for in Article 73 of Law Notary, and Article 26Peraturan Minister of Justice and Human Rights of the Republic of Indonesia Number M.02.PR.08.10 2004 then the number 2 point 2 of the Decree of the Minister of Justice and Human Rights of the Republic Indonesia No. M. 39-PW.07.10 2004. And the Central Supervisory Council (MPP) of Article 77, Article 84 and Article 85undang Notary Law, Article 29 of the Regulation of the Minister of Justice and Human Rights of the Republic of Indonesia Number M.02.PR.08.10 Year 2004dan item 3 item 1Keputusan Minister of Law and Human Rights human This study uses normative law research. The approach used approach to law (statute approach), the conceptual approach (conseptual approach) and approaches the case (case approach) Republic of Indonesia No. M.39-PW.07.10 200.